Current pathogens infecting open fracture tibia and their antibiotic susceptibility at a tertiary care teaching hospital in South East Asia. Issue 1 (March 2022) - Islam, Md. Samiul; Islam, Syed Shahidul; Parvin, Sultana; Manjur, Mushfique; Islam, Muhammad Rafiqul; Halder, Rabin Chandra; Islam, Mohd. Sayedul; Rahaman, Syed Khaledur; Hoque, Mobinul; Faruque, Md. Omar; Haque, A.K.M. Nazmul
Summary: Background: Tibia fractures represent the most prevalent open long-bone injuries. Indiscriminate, extensive, and unnecessary use of antibiotics has led to the emergence of infections caused by multidrug resistant organisms that increase morbidity and mortality. This study evaluated the spectrum of current organisms infecting the open tibia fractures and their antibiotic susceptibility pattern. This research did not alter the exiting practice of the institute to evaluate the current status. Methods: This was a cross-sectional study on 628 patients presenting with open fractures of the tibia from July 2018 to July 2020. Sampling for three successive culture (and sensitivity) tests were carried out, 1st on specimens taken in the emergency room (upon patient presentation), 2nd in the emergency theatre after initial debridement, and 3rd in the ward between 12 to 14 days post operatively. Results: The average age of the patients was 36.2± 15.4 years, with motor vehicle accidents being the predominant aetiology (72.2%). Results of specimen culture demonstrated that debridement could reduce microbial contamination significantly (P<.05) from 38.5 % to 26.4%. But from the ward sample, the infection rate was 45.1%, while contamination at entering the ward was only 26.4%. The bacteriological study found predominant multidrug-resistant Gram-negative organisms, namely Pseudomonas spp ., Escherichia coli, Klebsiella spp ., Acinetobacter spp ., Enterobacter spp . and Proteus spp . Though Gram-positive Staphylococcus aureus was found significantly in the initial culture, they contributed minimally (1.4%) to infect the fracture site. Conclusion: The current study found a predominant shift in the trend toward multidrug-resistant Gram-negative organisms in orthopaedic infection, which was accompanied by a worrying pattern of hospital-acquired infection. These results will help to inform future research and policies within our institution.